مظاهر العنف الأسري نتيجة جائحة كورونا وأثارها على الطفل - معزوز, هشام; فريحة, محمد كريم (جامعة الوادي - University of Eloued, 2023)
اهتمت هذه الدراسة بالتداعيات التي أفرزتها الإجراءات الاحترازية نتيجة الحالة الوبائية لتفشي فيروس كورونا منذ شهر مارس 2019، وقد أُريد من خلالها التعرف على مظاهر العنف الأسري والأطراف المسببة له وأثارها على الأطفال، ومن اجل تحقيق الأهداف المرجوة من البحث تم الاعتماد على المنهج الوصفي التحليلي كمنهج دراسة، والاستبيان بشكله الالكتروني كأداة لجمع البيانات، على عينة دراسة، قوامها 16 أسرة من مدينة عنابة (الجزائر)، سُجل عنف اسري مابين أفرادها أو اتجاه أطفالها في فترة الحجر الصحي، ومن بين أهم النتائج التي تم التوصل اليها، أن الظروف العامة التي أحيطت بالإجراءات الوقائية ولاسيما الحجر الصحي المنزلي أثرت على النسق الأسري، أين افرزت مشكلات اقتصادية واجتماعية ونفسية، كان أهمها العنف الأسري التي كان تأثير بشكل واضح على نفسية وسلوك الأطفال، وهذا في ظل قصور عمليات التكفل الأمثل من قبل الآباء لاطفالهم. This study is concerned with the implications of the precautionary measures as a result of the epidemiological situation of the outbreak of the Corona virus - covid-19 since March 2019, and through it I want to identify the manifestations of family violence and the parties causing it and their effects on children, and in order to achieve the desired objectives of the research, the approach Descriptive and analytical as a study method, and the questionnaire in its electronic form as a tool to collect data, on a study sample, consisting of 16 families from the city of Annaba (Algeria), recorded domestic violence between their members or the direction of their children during the quarantine period, and among the most important results that were reached, that the circumstances The general environment surrounding the preventive measures, especially home quarantine, affected the family pattern, where they generated economic, social and psychological problems, the most important of which was family violence that had a clear impact on the psychological and behavior of children, and this is in light of the insufficiency of optimal parenting processes for their children.
دراسة ميدانية بمدينة عنابة
مقال
Keywords: العنف الأسري؛ التاثير ؛ فيروس كورونا؛ النسق الاسري؛الطفل; Domestic Violence; the influence; ;the family pattern ; Corona Virus. Child